Host and Clostridioides difficile-Response Modulated by Micronutrients and Glutamine: An Overview - Loureiro, Andréa V.; Barbosa, Maria L. L.; Morais, Maria L. G. S.; Souza, Ismael P.; Terceiro, Letícia S.; Martins, Conceição S.; Sousa, Arkila P. R.; Leitão, Renata F. C.; Shin, Jae H.; Warren, Cirle A.; Costa, Deiziane V. S.; Brito, Gerly A. C. (Frontiers in Nutrition, 2022)
Changes in intestinal microbiota are integral to development of Clostridioides difficile (C. difficile)—associated nosocomial diarrhea. Certain diets, especially Western diets, increase susceptibility to C. difficile infection (CDI). Here, we discuss recent findings regarding how nutrients modulate response of the host and C. difficile during infection. Calcium has a role in the sporulation and germination process. Selenium is effective in reducing the total amount of C. difficile toxin A (TcdA) and toxin B (TcdB) and in decreasing its cytotoxicity. In addition, selenium phosphate synthetase deficiency reduces C. difficile growth and spore production. On the other hand, iron has a dual role in C. difficile growth. For instance, high intracellular levels can generate reactive hydroxyl radicals, whereas low levels can reduce its growth. In humans, zinc deficiency appears to be related to the recurrence of CDI, in contrast, in the CDI model in mice a diet rich in zinc increased the toxin's activity. Low vitamin D levels contribute to C. difficile colonization, toxin production, and inflammation. Furthermore, glutamine appears to protect intestinal epithelial cells from the deleterious effects of TcdA and TcdB. In conclusion, nutrients play an important role in modulating host and pathogen response. However, further studies are needed to better understand the mechanisms and address some controversies.